2008
DOI: 10.1007/s12070-008-0125-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxymetazoline plus dexpanthenol in nasal congestion

Abstract: Oxymetazoline and dexpanthenol combination has a better efficacy, shorter recovery time, causes lesser rebound congestion and has better tolerability than xylometazoline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Given the mechanism of action, it cannot be easily explained why dexpanthenol not only reduces the sign of redness and the symptom of rhinorrhea but also the swelling of the mucosa, leading to a strong reduction of the feeling of nasal blockage in most patients within 3 days. This antiobstructive synergy with a nasal decongestant, which has already been described by Jagade, although not under double-blind, placebo-controlled conditions, needs further clarification [ 20 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Given the mechanism of action, it cannot be easily explained why dexpanthenol not only reduces the sign of redness and the symptom of rhinorrhea but also the swelling of the mucosa, leading to a strong reduction of the feeling of nasal blockage in most patients within 3 days. This antiobstructive synergy with a nasal decongestant, which has already been described by Jagade, although not under double-blind, placebo-controlled conditions, needs further clarification [ 20 ].…”
Section: Discussionmentioning
confidence: 93%
“…While the effects of the use of nasal sprays containing decongestants alone mainly focus on the improvement of nasal obstruction, additional effects can be expected from adding a nurturing substance, such as dexpanthenol. These effects have been studied in two double-blind, active-controlled clinical trials comparing the monosubstance xylometazoline with the combination of dexpanthenol and xylometazoline [ 19 ], or oxymetazoline and dexpanthenol [ 20 ]. Kehrl et al showed that in patients suffering from acute rhinitis, the combined administration of xylometazoline and dexpanthenol was more effective than xylometazoline monotherapy in decreasing rhinorrhea, nasal obstruction, conchal swelling, and hyperemia of the nasal mucosa.…”
Section: Nasal Decongestants In Acute Rhinitismentioning
confidence: 99%
See 1 more Smart Citation
“…Решением для преодоления данного побочного действия является использование назальных сосудосуживающих препаратов без консер-вантов или добавление в препарат веществ, обладающих цилиопротективным эффектом [9,10]. Наилучшим реше-нием для уменьшения отрицательного воздействия деконгестанта и вспомогательных веществ, входящих в состав препарата, является использование комбиниро-ванных лекарственных средств с декспантенолом [11,12]. Еще одним возможным путем решения проблемы мест-ных побочных эффектов от применения назальных сосу-досуживающих препаратов является параллельное использование средств для ирригационно-элиминацион-ной терапии, в основном изотонических растворов сте-рильной морской воды [13].…”
unclassified
“…Консерванты, содержащиеся в составе большинства деконгестантов, будут усиливать уже существующую цилиарную дисфунк-цию, что обычно выражается в виде жалоб пациентов на жжение или сухость в полости носа после применения данных препаратов. Возможным решением данной про-блемы может стать применение назальных препаратов, не содержащих антисептиков, консервантов, или исполь-зование комбинированных лекарственных средств с декспантенолом [11,12].…”
unclassified